Analysis of Contribution and Comparison of Original Regional Income (PAD) of Lombok Tengah Regency Before and After the Development of the Mandalika Special Economic Zone - Yuni Arfatul Febria; Emi Salmah; Muhammad Alwi; Eva Wegner (Tinta Emas Publisher, 2024)
This research aims to analyze the contribution and comparison of Lombok Tengah Regency's Original Regional Income before and after the development of the Mandalika Special Economic Zone. This research uses quantitative methods. The location of this research is in Lombok Tengah Regency, while the research object is Regional Original Income before and after the development of the Mandalika Special Economic Zone. The data analysis used is contribution analysis and comparison tests using the paired sample t test. The research results show that: (1) The contribution of regional taxes before the construction of the Mandalika SEZ was 25.30% and 38.27% after the Mandalika SEZ construction. (2) The contribution of regional levies before the construction of the Mandalika SEZ was 10.60% and 8.16% after the construction of the Mandalika SEZ. (3) The contribution to regional wealth management results that were separated before the construction of the Mandalika SEZ was 5.25% and 4.67% after the construction of the Mandalika SEZ. (4) Other legitimate PAD contributions before the construction of the Mandalika SEZ were 58.85% and 51.43% after the Mandalika SEZ construction. (5) There is a difference in regional taxes before and after the construction of the Mandalika SEZ with a significance value of 0.010. (6) There are no differences in regional levies, results of separated wealth management, other PAD and local original income before and after the construction of the Mandalika SEZ with significance values of 0.788, 0.896, 0.786, 0.377.